A road toward better education in personalized medicine at universities and beyond. (June 2015) - Marie, Karlikova; Jiri, Polivka; Jan, Strojil; Ondrej, Topolcan
Personalized medicine is likely to become a future direction of medicine. There is increased knowledge about gene functions in human health and disease and a rapid advance of biotechnologies. Personal genetic testing is available outside the medical room, as direct-to-consumer testing. There is concern about genetic literacy of general public and healthcare professionals which are to handle genetic results and their clinical interpretation. Education and training in personalized medicine and genetic/genomics/pharmacogenomics issues at different levels (high school, university, continuing medical education) is needed. Examples of innovated educational tools and curricula over the world are presented. The educational initiatives in the field of personalized medicine in the Czech Republic are followed from the very beginning.